The climate of the Campos de Cima da Serra Region, Rio Grande do Sul sate, Brazil: thermal and water conditions - Pereira, Tatiane Paiva (2009)
This work has the objec ve to make available informa on about the climate of Campos de Cima da Serra Region, in Rio Grande do Sul State, Brazil, focusing on thermal and water condi ons. Data from meteorological sta ons located in Bom Jesus, Lagoa Vermelha, and Vacaria were used for analyzing the air temperature, pluvial precipita on, and number of rainy days, taking into accounts the meteorological series from 1931 to 1990. Several basic sta s cs and temporal tendencies were determined. In according to the annual varia on of the global solar radia on, the thermal oscilla on showed that July is the coldest month and January is the warmest month. The monthly average air temperature ranged from 11.4 C to 22.1 C. The monthly average pluvial precipita on ranged from 101mm to 174mm, while the number of rainy days had ranged from 9 to 16 days a month. Tendencies of decreasing the maximum air temperature and of increasing the minimum air temperature and the number of rainy days were observed.